Pomegranate 13 (August 2000) - (:unkn) unknown (The Pomegranate, 2000)
Readers' Forum. Don Frew's Harran Hypothesis -- Spells, Saints, and Streghe: Witchcraft, Folk Magic, and Healing in Italy / by Sabina Magliocco -- Blót on the Landscape: Re-reading Pope Gregory's Letter on the Heathen Temples / by Jeremy Harte -- Shamanistic Elements in Zoroastrianism: The Pagan past and Modern Reactions / by Touraj Daryaee -- Mirra Alfassa: A Western Occultist in India / by Christine Rhone -- Book Reviews: The Myth of Matriarchal Prehistory: Why an Invented Past Will Not Give Women a Future by Cynthia Eller / first review by Laurel Holmström ; second review by Wendy Griffin
The Pomegranate: A New Journal of Neopagan Thought
1 Electronic record(s) and derivatives. PDF 1.7 (Acrobat 8.x). 30 pages. 4378473 bytes.
Keywords: Harran (Turkey)--History--To 1500; Witchcraft--Italy; Folk magic--Italy; Gregory I, Letter to Abbot Mellitus; Gregory I, Pope, approximately 540-604--Criticism and interpretation; Sculpture--Mutilation, defacement, etc.--England--Religious aspects--Christianity; Zoroastrianism--Customs and practices; Periodicals; Shamanism--Relations--Zoroastrianism; Mother, 1878-1973--Influence; Eller, Cynthia, 1958- Myth of matriarchal prehistory--Reviews; Book reviews; Literary criticism